E-Learning in Indonesia - R. A. Indrawati (Journal of Indonesian Scholars for Social Research, 2022)
As part of this research, students rated the e-learning module on the LMS. We give substantial qualitative interview data. General satisfaction and disapproval questions indicate student assessment criteria, whereas module-specific questions reveal student learning processes. Lesson topics, discussion forums, student interactions, and other learning tools are utilized by students to show pleasure. Topics of discontent include platform robustness and usability, study materials (articles and books), and student workloads. The flow of debate and engagement is appreciated, but students are worried about participating, and expectations regarding the role of lecturers in e-learning haven't been developed.